Republic of Slovenia : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2012)
The Slovenian financial system has been hard hit by the crisis. Banks remained highly vulnerable to continued credit deterioration and refinancing risks. Strengthening of financial condition of banks should be the short-term priority. The financial restructuring should be followed by privatization of state-controlled banks. The supervision of financial institutions should be complemented with a macroprudential overview geared toward overall stability of the financial system. The crisis preparedness and management framework should be improved, and risks to systemic financial stability should be identified.